Analisis Citra Merek, Periklanan dan Word of Mouth terhadap Keputusan Pembelian Kosmetik Wardah - Octavia, Ayu Nurafni; Erlinda, Debby; Lau, Meliana Putri (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The purpose of this research is to find out whether the brand image. Advertising, word of mouth has an effect on purchasing decisions on buying wardah cosmetics. The population in this study were 100 case study respondents from students majoring in management at the University of Semarang and were included in the sample of this study. The research method to be carried out is quantitative research. The type of data used is primary data. Methods of data collection using questionnaires and documentation. The analysis technique used is the validity and reliability test, the classical assumption test (normality test, multicollinearity test and heteroscedasticity test), t test, F test and the coefficient of determination (R2). Test the hypothesis of this study with the help of SPSS version 23. The results of this study indicate that partially there is no effect between brand image variables and purchasing decision variables on wardah cosmetics, there is a significant positive effect between advertising variables and purchasing decision variables on purchasing wardah cosmetics, and there is significant positive effect between the word of mouth variable and the purchase decision variable on the purchase of wardah cosmetics. in the simultaneous test of brand image, advertising and word of mouth variables have a significant effect on purchasing decisions. In the determination test it is known that the purchase decision variable can be explained by the independent variable of 76.3% and the rest is explained by other variables outside the model